Strategi Perencanaan Konten dalam Manajemen Media Sosial Instagram Klien @bikinwebsite.co di PT Lopokopi Digital Shankara - Sabyla, Firyal Alfairuz; Hadiyanto, Hadiyanto (Universitas Islam Balitar, 2025)
This research analyzes the content planning strategy implemented by PT Lopokopi Digital Shankara for client @bikinwebsite.co, in increasing brand awareness through Instagram social media. The purpose of this research is to find out the process of preparing content planning and the right strategy to use. This research uses a descriptive qualitative approach with data collection techniques through interviews with the CEO, Growth Specialist, and Head of Social Media of PT Lopokopi Digital Shankara, with Media Production Management Theory with the POAC approach (Planning, Organizing, Actuating, Controlling). The results showed that content planning is based on client needs, target audiences, and social media trends by prioritizing educational and interactive content. The strategy implemented is proven to increase engagement and strengthen the brand identity of @bikinwebsite.co. This research contributes to the understanding of content management in the context of digital agencies and the importance of a structured communication strategy.